Allelopathic potential of cassava (Manihot esculenta L.) extracts on germination and seedling growth of selected weeds and aerobic rice - Siti Aisyah Mohammad Taupik,; Siti Nur Anisah Aani,; Chia, Poh Wai; Chuah, Tse Seng (Penerbit Universiti Kebangsaan Malaysia, 2022)
Weed infestation is a major problem in the aerobic rice system due to the lack of standing water that could prevent the growth of weeds. To reduce heavy reliance on herbicide, this research aims to determine the potential of cassava allelopathy for inhibition of weeds in aerobic rice. The allelopathic potential of cassava extracts on the germination and growth of tested weed species (Eleusine indica, Ageratum conyzoides, and Cyperus distans) and aerobic rice (Oryza sativa) was conducted in the laboratory. The results showed that increasing the aqueous extract concentrations of cassava extracts inhibited the germination and seedling growth of tested weeds, suggesting the allelopathic effects of cassava extracts are concentration dependent. The degree of phytotoxicity of different vegetative parts of cassava can be classified in order of decreasing inhibition as follows: leaf, stem, tuber, and tuber peel. Aqueous leaf extract of cassava at a concentration of 0.5% (w/v) provided complete inhibition on A. conyzoides, E. indica, and C. distans germination whereas 25% to 100% inhibition on the shoot growth was recorded. By contrast, the shoot growth and germination of aerobic rice were not affected. These results suggest that the cassava leaf extracts contain water-soluble allelochemicals for inhibition on A. conyzoides, E. indica, and C. distans in aerobic rice.